Mineral Deficiencies - Electrolyte Disturbances, Genes, Diet and Disease Interface 2021
DOI: 10.5772/intechopen.94276
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Deficiencies: A Root Cause for Reduced Longevity in Mammals

Abstract: Metals, inorganic compounds and their elements that act as cofactors for enzymes that play an essential role in various biological processes constitute mineral nutrients. Their primary source is soil and enters the climax consumers in food chain through plants as they contain most minerals that are essential for humans. They are required in small and precise amounts according to their requirement they were classified as Major (phosphorous (P), potassium (K)), Secondary (calcium (Ca), magnesium (Mg), sulphur (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 110 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Na (ranging from 223.92–246.99 mg/100g) and K (ranging from 211.04–178.45 mg/100g) appear to be the most abundant, while P (ranging from 1.78–1.92 mg/100g) and Mn (ranging from 1.14 to 1.64 mg / 100g) appear least abundant in the melon seed flour of this study, corroborating the data reported elsewhere [ 3 ]. The function of P is for bone mineralization and energy transfer, Ca for bone development and growth, Mg for cardiac and smooth muscle contractibility, K for contraction of smooth, skeletal, and cardiac muscle, as well as Na for nerve transmission and regulation of fluid balance [ 25 ]. Mn is a cofactor for enzymes involved in carbohydrate metabolism, Fe synthesizes hemoglobin and myoglobin, and Zn serves as an antioxidant defense function and synthesis of DNA/RNA [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Na (ranging from 223.92–246.99 mg/100g) and K (ranging from 211.04–178.45 mg/100g) appear to be the most abundant, while P (ranging from 1.78–1.92 mg/100g) and Mn (ranging from 1.14 to 1.64 mg / 100g) appear least abundant in the melon seed flour of this study, corroborating the data reported elsewhere [ 3 ]. The function of P is for bone mineralization and energy transfer, Ca for bone development and growth, Mg for cardiac and smooth muscle contractibility, K for contraction of smooth, skeletal, and cardiac muscle, as well as Na for nerve transmission and regulation of fluid balance [ 25 ]. Mn is a cofactor for enzymes involved in carbohydrate metabolism, Fe synthesizes hemoglobin and myoglobin, and Zn serves as an antioxidant defense function and synthesis of DNA/RNA [ 26 ].…”
Section: Resultsmentioning
confidence: 99%